Perceived Utility of Information and Communication Technologies in Agricultural Extension System - Raksha , I Sreenivasa Rao; Shaik N Meera (Indian Journal of Extension Education, 2015)
A study was carried out in Ranga Reddy district of Andhra Pradesh to get the perception of extension personnel towards utility of information and communication technologies in agricultural extension. Total 180 respondents were taken for the study. A list of different ICTs was made with their possible diverse uses in agricultural extension system viz, planning, monitoring, evaluation, group discussion, exhibition, discussion, field visit, training, lecture etc. The findings showed that respondents have positive perception towards the use of ICTs tools in agricultural extension system and its use depends on the needs and utility of the ICTtools as per the purpose served.